Investigation of an autologous blood treatment strategy for temporomandibular joint hypermobility in a pig model - Stembirek, J; Matalova, E; Buchtova, M; Machon, V; Misek, I (International journal of oral and maxillofacial surgery, 2013)
Many different surgical and non-surgical techniques are used for the treatment of temporomandibular joint (TMJ) hypermobility. One of these methods is autologous blood injection into the TMJ. The fate of the autologous blood used for treatment of recurring condylar dislocation is still not completely understood. The authors used 12 pigs (Sus scrota f. domestica) as a model species for autologous blood delivery into the TMJ. Blood injection was followed by histopathological analysis at different times after treatment (1h, 1, 2 and 4 weeks). Samples were examined by magnetic resonance imaging, macroscopic and histological methods. The deposition of the remaining blood was observed in the form of clots in the distal parts of the upper joint cavity 1h and 1 week after treatment. 2 weeks after treatment, small blood clots were still apparent in the distal part of the upper joint cavity. 4 weeks after surgery, no remnants of blood, changes or adhesions were apparent inside the TMJ. No morphological or histological changes were observed in the TMJ after the injection of autologous blood suggesting another mechanism is involved in the hypermobility treatment.
Keywords: injekce intraartikulární; krev; Longitudinal Studies; Temporomandibular Joint; autologní krevní transfuze; Sus scrofa; zvířata; Joint Dislocations; Temporomandibular Joint Disorders; Blood Transfusion, Autologous; dislokace kloubu; hemokoagulace; temporomandibulární kloub; Synovial Fluid; nemoci temporomandibulárního kloubu; longitudinální studie; Blood Coagulation; paracentéza; Blood; Injections, Intra-Articular; Animals; Paracentesis; Disease Models, Animal; synoviální tekutina; modely nemocí na zvířatech